Association between the use of oral contraceptives and the occurrence of systemic hypertension: A systematic review with statistical comparison between randomized clinical trial interventions - Ingrid Soares de Souza; Gabriel Zorello Laporta; Juliana Zangirolami-Raimundo; Isabel Cristina Esposito Sorpreso; Heloisa Carla Lopes Silva dos Santos; José Maria Soares Júnior; Rodrigo Daminello Raimundo (Elsevier, 2024)
Introduction: In the WHO eligibility criteria, there is agreement that hypertensive women taking Oral Contraceptive Hormonal Combined (OCHC) may be at increased risk of cardiovascular disease. The risk-to-benefit ratio hinges on the severity of the condition. While a mild increase in blood pressure is a common occurrence in consumers of OCHC, the potential for developing high blood pressure exists during oral contraceptive use. Consequently, there is a possibility of increased cardiovascular risk, with limited available data on this issue. Objective: To evaluate the potential effects of OCHC on blood pressure through a systematic review with statistical analysis of existing randomized controlled trials. Method: This systematic review with statistical comparison adheres to the recommendations outlined in the PRISMA (Principal Reporting Items for Systematic Reviews and Meta-analyses) guidelines. The analysis strategy involves comparing the mean difference in blood pressure change according to the type of treatment, in addition to the calculation of clinically relevant outcomes (CRO). Results: Our findings suggest a clinically relevant outcome related to the increase in blood pressure in users of ethinyl estradiol combined with gestodene in a cyclic regimen over 6 months. Conversely, a decrease in blood pressure was observed among users of ethinyl estradiol combined with chlormadinone over 24 months of usage. Conclusion: While our study found minor variations in blood pressure across varying forms of oral contraceptives, these differences are not significant enough to warrant specific clinical recommendations. However, the results suggest that individuals with hypertension should exercise caution with ethinyl estradiol, particularly when administered cyclically alongside gestodene, due to the potential risk of increased blood pressure. Additionally, the use of oral contraceptives containing ethinyl estradiol paired with chlormadinone acetate or ethinyl estradiol combined with drospirenone may be more suitable for individuals at a high risk of developing hypertension.